High Bullying Exposure and Depression Risk Among Indonesian Adolescents in Boarding Schools: Multivariate Insights from a Cross-Sectional Study - Funna, Rizkia; Tahlil, Teuku; Aiyub, Aiyub (Queeva Publishing, 2025)
Background: Bullying is an aggressive behavior that negatively impacts students' mental health, potentially leading to depression. Boarding school environments are marked by intense peer dynamics, which may facilitate the occurrence of various forms of bullying. Methods: This cross-sectional study employed a quantitative approach involving 296 Indonesian boarding school students selected through multistage random sampling. Data were collected using the Form of Bullying Scale (FBS) and the depression subscale of the Depression, Anxiety, and Stress Scale (DASS-21). Descriptive and inferential statistics were used, including simple and multivariate logistic regression. Initial multivariate modeling included age, grade level, parental occupation, and parental income; however, only gender and bullying level remained significant and were retained in the final model. Results: The findings revealed that 38.5% of students experienced a high level of bullying, and 43.6% were identified as experiencing depression, with most cases classified as mild to moderate. Multivariate analysis showed that female gender (AOR = 3.716, p < 0.001) and high bullying exposure (AOR = 3.379, p < 0.001) significantly increased the risk of depression. Conclusion: Depression is prevalent among boarding school students, with over one-third also reporting high levels of bullying. Gender and bullying exposure were identified as key risk factors. These findings highlight the need for targeted preventive and promotive interventions, such as peer support programs, resilience workshops, and school staff training, focusing on strengthening students’ mental resilience and implementing gender-based anti-bullying strategies within the boarding school environment.